Evaluating safety of genetically modified crops: effect of Bt-transgenic cabbage plants on microbial dynamics and dehydrogenase activity - DUTTA, DEBASHIS; GOPAL, MADHUBAN; SHUKLA, LIVLEEN; MAHAJAN, V K (The Indian Journal of Agricultural Sciences, 2012)
The fear that Bt transgenic cabbage may secrete some toxic or inhibitory substance that will adversely affect the populations of microorganisms dwelling in its rhizosphere did not appear to be true. Though only the culturable microbial population constituting less than 1% of the soil bacteria was examined, the study proved that Bt transgenic was not adversely affecting the representative culturable microorganisms dwelling around their rhizosphere in soil.